STRATEGI KOMUNIKASI POLISI RESORT KOTA PEKANBARU DALAM MENSOSIALISASIKAN APLIKASI POLISI ZAPIN - Yona Setiawati; Muhammad Firdaus; Ismandianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Internet technology is growing, all internet-based average orientation activities, and many applications began to be developed and utilized in everyday life. Relating to the development of the internet and communication technology currently affects all fields, including the opening of channels of information and communication in all aspects. One of them is within the scope of the Police, this is very important to be applied as a means of delivering information and improving services through an android-based application. Crime in Pekanbaru is a problem that will never end. In order to overcome the problem of criminality and as a way to increase service, Polisi Resor Kota Pekanbaru created the Zapin Police application that serves to provide complaints information services. This research aims to determine the strategies of communicators, audience strategy, Message planning and media selection Polisi Resor Kota Pekanbaru in socialize Zapin Police application.This research uses qualitative research methods with the presentation of descriptive analysis, namely by describing the state of the subject or object of research based on the facts that appear. The informants in this research were 6 people taken based on purposive techniques. The data collection technique used is semi structured interview, non-participant observation and documentation of drawings, notes and photographs of activities carried out by the Polisi Resor Kota Pekanbaru relating to this research. The interactive data analysis model the author uses to describe the results of the research in data analysis techniques and for checking the validity of the data the researcher uses the triangulation technique and the extension of participation.The results of the research showed that the communication strategy of the Polisi Resor Kota Pekanbaru chose a communicator in disseminating the Police Zapin application, which had credibility and power. Determination of the target audience, namely the entire community of the city of Pekanbaru, especially those who have an Android smartphone and have a resident card (KTP), the placement of the target audience is divided into 3 segments, namely institutions / agencies, youth and the general public. Message planning is used directly to the core of the message, and through 2 message organizing formats namely topical format, spatial format and problem solving. Then the media selection is divided into media personally, namely directly and nonpersonally through mass media and group media.Keyword : Communication Strategy, Criminality, The Police Zapin Application